1997
DOI: 10.1007/s003590050089
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia attracts the haematophagous bug Triatoma infestans : behavioural and neurophysiological data on nymphs

Abstract: 1) Nymphs of the haematophagous bug Triatoma infestans (Heteroptera: Reduviidae) are attracted to volatiles from their own faeces on a servosphere. 2) Biological substrates attractive to triatomines release NH 3 : wetted triatomine faecal papers release NH 3 at 256 ppb NH 3 from a 60-g source and stale rabbit urine at 394 ppb from 200 ml. Ammonia released from aqueous NH 3 also attracts bugs at doses of 3 ppb and 17 ppb on the servosphere. 3) Bugs typically show negative anemotaxis in a stimulus-free air-strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 53 publications
4
77
0
1
Order By: Relevance
“…8 and 9). The existence of two functional GP sensilla sub-types as described by Taneja and Guerin (1997) was confirmed here (Table 1, Figs. 13 and 14).…”
Section: The Auxiliary Cells and Sensillum-lymph Cavitiessupporting
confidence: 85%
See 4 more Smart Citations
“…8 and 9). The existence of two functional GP sensilla sub-types as described by Taneja and Guerin (1997) was confirmed here (Table 1, Figs. 13 and 14).…”
Section: The Auxiliary Cells and Sensillum-lymph Cavitiessupporting
confidence: 85%
“…In addition, the authors confirmed the presence of two functionally different GP sensilla sub-types first suggested by Taneja and Guerin (1997): type 1 housing an NH 3 -excited receptor neurone and type 2 housing an NH 3 -excited cell in addition to a neurone responding to short-chain carboxylic acids such as isobutyric acid, present in host odour (Guerenstein, 1999).…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations